A systematic review of the effectiveness of clinical nurse specialist interventions in patients with chronic obstructive pulmonary disease (COPD) - Yin Hua; Yang Ling; Ye Qiao (Sciendo, 2018)
This review aimed to examine the effectiveness of clinical nurse specialist (CNS) interventions in patients with chronic obstructive pulmonary disease (COPD). COPD significantly affects people's health worldwide. With the development in nursing, CNSs are playing increasingly important roles in different departments. However, the studies on the effectiveness of CNSs in COPD are not as well organized as the studies on the effectiveness of CNSs in bronchiectasis and asthma. Therefore, this review aims to find some updated evidence on the CNS interventions for patients with COPD and on whether these interventions are effective.